STUDI PARAMETER KELAYAKAN USAHA PENCAIRAN BATUBARA DI INDONESIA - Adhi Dharma Permana (Badan Pengkajian dan Penerapan Teknologi, 2011)
Coal liquefaction technology holds promise to provide synthetic liquid fuels as a substitute for conventional liquid fuels. For the purpose of application of a hig investment and advance technology, such as coal liquefaction technology, the competitiveness of its product need to be assessed before pursuing a commercial venture. The market of coal liquefaction technology is the oil fuels market of which its price is volatile. This paper proposes a techno-economical assessment of the Brown Coal Liquefaction tecnology through a base case calculation and a series of scenarios to perform sensitivity analysis of various parameters deemed crucial to its competitivenss.Â Kata Kunci: coal liquefaction, BCL, investment cost, sensitivity analysis, policy Strategy